Human resource management and labour relations in post-transitional Russia - Elena Shulzhenko (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2012)
The paper discusses the role of the personnel function as described in the research literature before the background of the particular characteristics of the Russian HR conditions which have evolved during the transition period. It describes the characteristics of wage and incentive systems in Russian private enterprises, of personnel development systems, and of work organisation on the shop floor. Leadership styles and work- behaviour and work values are discussed as well as industrial relations literature dealing with the role of unions and of collective bargaining and with the perception of trade unions by employees. It ends with a brief summary and some conclusions.
Keywords: 330